2019
DOI: 10.2174/1874210601913010267
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Assessment of Peri-implantitis Treatment Procedures: A Review

Abstract: Background: The prevalence of peri-implantitis is increasing continuously and such a biological complication significantly decreases implant survival and success. Although various treatment modalities have been identified for peri-implantitis, no completely efficient method has yet been established. Objective: The aim of this review was to evaluate the scientific literature regarding the in vitro effects of peri-impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…29 Although it is not always possible to completely replace animal models with in vitro techniques, it is advisable that non-animal experiments are carried out to collect initial data and thus refine the design of subsequent preclinical studies. In a review of in vitro studies focused on the treatment of peri-implantitis, Benli et al 30 concluded that titanium discs, sectioned implants and titanium surfaces were commonly used as test samples. A limitation of this type of method is that cells are seeded on a horizontal surface — and this does not correspond to the clinical ( in vivo ) environment.…”
Section: Discussionmentioning
confidence: 99%
“…29 Although it is not always possible to completely replace animal models with in vitro techniques, it is advisable that non-animal experiments are carried out to collect initial data and thus refine the design of subsequent preclinical studies. In a review of in vitro studies focused on the treatment of peri-implantitis, Benli et al 30 concluded that titanium discs, sectioned implants and titanium surfaces were commonly used as test samples. A limitation of this type of method is that cells are seeded on a horizontal surface — and this does not correspond to the clinical ( in vivo ) environment.…”
Section: Discussionmentioning
confidence: 99%
“…Gramnegative bacteria and lipopolysaccharide body (LPS) of anaerobic bacteria are known to play a significant role in peri-implantitis. [11][12][13]47,48 Besides, enteric bacteria also seem to take part in the process, being identified in periimplantitis sites before. 49 E. coli is a Gram-negative facultative anaerobic bacterium that was validated to adhere to titanium surfaces at in vitro experiments, being a good alternative to avoid the difficult control over growth environment at anaerobic culture.…”
Section: Discussionmentioning
confidence: 99%
“…Our decision for using E. coli was based on the necessity of a simple bacteria culture that provides an inoculation of easy control and stability on the microimplant surface, whereas the cultivation of anaerobic bacteria is more complex and sensitive. The use of E. coli as a Gram‐negative culture for implant decontamination assays is a common practice, 47–49 which can be justified by some factors. Gram‐negative bacteria and lipopolysaccharide body (LPS) of anaerobic bacteria are known to play a significant role in peri‐implantitis 11–13,47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A margem gengival ao redor do implante pode ser composta por mucosa ceratinizada ou não ceratinizada (WU, Q. et al, 2015). Nesta região, as fibras colágenas do tecido conjuntivo se posicionam paralelamente à superfície do implante, propiciando maior vulnerabilidade frente à inflamação induzida por placa (BERGLUNDH et al, 1991;BUSER et al, 1992). A presença de faixa de tecido ceratinizado pode atenuar este efeito, reduzindo a probabilidade de quadros de periimplantite (LIN; CHAN;WU, Q. et al, 2015).…”
Section: Lista De Figurasunclassified